The works of Guillermo Furlong S.J. and the archive of the Argentine-Uruguayan Province of the Society of Jesus: a window to unknown documentary collections (Quinto Sol, 2023)
After the expulsion of the Society of Jesus from the Río de la Plata, its documentary collections suffered a process of fragmentation: throughout the 19th century, they were moved on numerous occasions until they were deposited in various national and provincial archives. After its restoration, in the mid-19th century, the Society reconstructed its archives locally and globally. The central institution is the Archivum Historicum Societatis Iesu (Rome), which collects documentation from all the provinces of the order; At the same time, there are numerous provincial archives that complement it. However, one remains closed today: the Archive of the Argentine-Uruguayan province of the Society of Jesus, in Buenos Aires. Part of the information contained in it can be reconstructed since it has nourished the research of one of the main historians of the Company in Argentina, Guillermo Furlong. In this work, a transversal analysis of some of his most significant works is carried out to trace those documents used by Furlong with the aim of reconstructing the contents of an archive that, without a doubt, contains essential material for the study of the history of the Society of Jesus in the region.
Keywords: Jesuits; archive; documentary collections; River Plate